2017
DOI: 10.2147/jpr.s122255
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of depression in participants with nonspecific acute or subacute low back pain and no-pain by age distribution

Abstract: Background and purposeNonspecific low back pain (LBP) is the most prevalent musculoskeletal condition in various age ranges and is associated with depression. The aim of this study was to determine the Beck Depression Inventory (BDI) scores in participants with nonspecific LBP and no-pain by age distribution.MethodsA case–control study was carried out following the Strengthening the Reporting of Observational Studies in Epidemiology criteria. A sample of 332 participants, divided into the following age categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
(46 reference statements)
1
18
0
1
Order By: Relevance
“…In addition, our study showed that age and the HV deformity degree were shown as predictors for kinesiophobia symptoms and pain intensity. These findings were in accordance with prior studies reporting that psychological disorders were linked to musculoskeletal conditions, increasing this association with greater age distribution [8][9][10][11][12][13]. In addition, greater instability was shown in older adults under musculoskeletal disorders [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, our study showed that age and the HV deformity degree were shown as predictors for kinesiophobia symptoms and pain intensity. These findings were in accordance with prior studies reporting that psychological disorders were linked to musculoskeletal conditions, increasing this association with greater age distribution [8][9][10][11][12][13]. In addition, greater instability was shown in older adults under musculoskeletal disorders [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
“…Several psychological disorders, such as depression or sociability and vigor linked to general health-related quality of life alterations, have been associated with musculoskeletal conditions, which may increase with greater age ranges [8][9][10][11][12][13]. In addition, musculoskeletal disorders of the lower limbs may alter body stability, showing a greater instability in older adults [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…За даними численних досліджень, депресія поєднується із хронічним болем у 11-50% випадків і супроводжується посиленням болю, зниженням якості життя, підвищенням інвалідності та вартості лікування (Munce and Stewart, 2007;Bair et al, 2008;Calvo-Lobo et al, 2017). При цьому як депресія, так і хронічний біль у жінок спостерігаються частіше, ніж у чоловіків (Bair et al, 2008;Tonelli et al, 2011).…”
Section: вступunclassified
“…Depression, a highly prevalent, costly, and disabling condition [6], is commonly seen in patients with subacute LBP [7][8][9]. In 2018, LBP was the first and depressive disorders the third leading worldwide cause of years lived with disability [6].…”
mentioning
confidence: 99%
“…In 2018, LBP was the first and depressive disorders the third leading worldwide cause of years lived with disability [6]. Currently, it is not quite clear whether depression is a cause of LBP: Cross-sectional data among sub-acute patients with LBP indicates that men and women with LBP have significantly higher depression score compared to those with no pain [7]. The prospective findings on the course of acute and subacute LBP suggest that depression might have an adverse effect on the prognosis of LBP [8].…”
mentioning
confidence: 99%